Evidence for the aetiology of human papillomavirus in oesophageal squamous cell carcinoma in the Chinese population: a meta-analysis. Issue 11 (15th November 2013) - Liyanage, Surabhi S; Rahman, Bayzidur; Gao, Zhanhai; Zheng, Yang; Ridda, Iman; Moa, Aye; Newall, Anthony T; Seale, Holly; Li, Qian; Liu, Jun-Feng; MacIntyre, C Raina
Abstract : Objectives: We aimed to conduct a meta-analysis of human papillomavirus (HPV) as a risk factor for oesophageal squamous cell carcinoma (OSCC) in China, using all eligible studies published in the English and Chinese language literature. Design: The random effect model was used to analyse the pooled OR. The I 2 and Q tests were included in the subgroup analyses. Setting: Literature searches of databases including MEDLINE, PUBMED, EMBASE and Chinese National Knowledge Infrastructure (CNKI) and other available resources were performed to retrieve studies investigating OSCC tissue from Chinese participants for the presence of HPV DNA. Primary outcome measure: A collective analysis of OSCC cases and control specimens was carried out from 15 case–control studies (6 in the English language and 9 in the Chinese language) for HPV prevalence. Results: Of a total of 1177 OSCC and 1648 oesophageal control samples, 55% (642/1177) of cancer specimens and 27% (445/1648) of control samples were positive for HPV DNA. A positive strong association between HPV DNA and OSCC was observed among the included studies, with a pooled OR of 3.69 (95% CI 2.74 to 4.96). Heterogeneity and publication bias were not observed in the analysis. Subgroup analyses of the included studies also supported the measure of association of causal links between HPV and OSCC. Conclusions: This meta-analysis provides the strongest evidence until now of an association between HPV and OSCC in the Chinese population. China has a high burden of OSCC, making this an important research finding. A strength and new contribution of this study is combining data from the English and Chinese language literature to analyse all studies conducted in China. These findings may inform the population level use of prophylactic HPV vaccination to reduce the burden of OSCC in China.